How Defined, Benefit Pension Assets Affect the Returns and Volatility of the Sponsor’s Stock (International Journal of Banking and Finance, 2008)
In its valuation of firms with defined benefit plans, the stock market combines changes in the valuation of pension assets with changes in the valuation of the net core assets. Unfortunately, aggregating the two disparate asset classes in valuation discards information about both classes. This work shows that by extracting the pension component of returns, two types of insights result: first, an enhanced understanding of the underlying risk and return of the firm’s net core assets; and, second, an enhanced perspective of the potential benefit from incorporating pension asset allocation into overall risk management.